2022
DOI: 10.15282/ijame.19.1.2022.12.0731
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Crashworthiness Criteria based on Variation of Hole as Crush Initiator in Thin-Walled Square

Abstract: Crashworthiness is the ability to protect its occupant by absorbing the energy of impact during a collision. A crush initiator is one way to increase crashworthiness criteria at collision. The most widely applied crush initiator applications are holes, wall thickness reduction, grooves, notch, bead and corrugated. This study discussed making a functional model from the crashworthiness criteria which is known by CFE and SEA. Variable used variations of the crush initiator in the form of circular holes with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Surface roughness plays an important role in mechanical properties, especially in machining jobs that require high precision [40] and display product characteristics [41]. The process of using journal.ump.edu.my/ijame ◄ an MQL Fan chip compared to dry milling is more profitable and can reduce the operational coolant [42], resulting in a cleaner and healthier environment [43,44].…”
Section: Surface Roughness Evaluationmentioning
confidence: 99%
“…Surface roughness plays an important role in mechanical properties, especially in machining jobs that require high precision [40] and display product characteristics [41]. The process of using journal.ump.edu.my/ijame ◄ an MQL Fan chip compared to dry milling is more profitable and can reduce the operational coolant [42], resulting in a cleaner and healthier environment [43,44].…”
Section: Surface Roughness Evaluationmentioning
confidence: 99%
“…Improvement of reliability and crashworthiness of motorized vehicles in advanced industries such as automotive, aeronautic, naval, etc., has been a big challenge for manufacturers. Thin-walled tubes were utilized as one of the best options to absorb the impact energy during a collision [ 1 ]. By the means of cost-effective tube products, various crash boxes have been made of available metals in the market, e.g., steel and aluminium alloys [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subramaniyan et al (2014) found that the quantity of circular cut-outs contributed to decreasing the PF in circular and square tubes. Other studies examined the impact of crush initiator placement, such as drilling holes (Estrada et al, 2019) and multiple holes (Malawat et al, 2019;Dionisius et al, 2022) in square steel tubes, leading to improved crashworthiness performance. Researchers have examined the use of V-notch, groove (Balaji and Annamalai, 2017), and tapered (Asanjarani et al, 2018) shapes as effective crush initiators, reducing the initial force spikes without compromising the total energy absorption.…”
mentioning
confidence: 99%